Efficient Inhibition of Pathologic Angiogenesis using Combination Therapy of Anti-Epcam and Anti-VEGFR2 Nanobodies - Karami, Elmira; Azizi, Parisa; Behdani, Mahdi; Kazemi-Lomedasht, Fatemeh (Current Pharmaceutical Design, 2023)
Background: EpCAM and VEGFR2 play an important role in angiogenesis and tumorigenesis. It is currently of paramount importance to produce new drugs that can inhibit the angiogenesis and proliferation of tumor cells. Nanobodies are potential drug candidates for cancer therapy due to their unique properties. Objective: This study aimed to investigate the combined inhibitory effect of anti-EpCAM and anti-VEGFR2 nanobodies in cancer cell lines. Methods: Inhibitory activity of anti-EpCAM and anti-VEGFR2 nanobodies on MDA-MB231, MCF7, and HUVEC cells was investigated using both in vitro (MTT, migration, and tube formation assays) and in vivo assays. Results: Results showed that the combination of anti-EpCAM and anti-VEGFR2 nanobodies efficiently inhibited proliferation, migration, and tube formation of MDA-MB-231 cells compared to each individual nanobodies (p < 0.05). In addition, the combination of anti-EpCAM and anti-VEGFR2 nanobodies efficiently inhibited tumor growth and volume of Nude mice bearing MDA-MB-231 cells (p < 0.05). Conclusion: Taken together, the results indicate the potential of combination therapy as an efficient approach to cancer therapy.
Keywords: EpCAM